The Use of Instagram for Promoting Private Higher Education In Jakarta Indonesia - Ulfa, Marwa; Hariyati, Farida; Akbari, Deni Adha (UPT Publikasi Ilmiah UNISBA, 2023)
Social media is used by various organizations, including private universities, for various promotional activities. Muhammadiyah University Prof. Dr. HAMKA (UHAMKA) as one of the largest universities in Jakarta Indonesia uses social media to share various kinds of information. This paper analyzes the use of Instagram in promoting private universities. This study uses a qualitative approach, supplemented by content analysis based on big data, accompanied by in- depth interviews with members of the UHAMKA Bureau of Promotion and New Student Admissions who are responsible for managing promotional content on the @uhamkatv Instagram account. The findings reveal that there are several factors that have a significant influence on the performance of Instagram content, namely (1) post type: according to Virol’s application analysis, images tend to perform better than videos in terms of engagement and reach. ; (2) format: albums tend to perform better than other formats, such as stories or reels; (3) the theme has a significant impact on engagement; (4) emotion: content that makes people feel happy, inspired, or entertained is usually better than other types of content; and (5) consistency: consistent posting frequency and timing are critical to maintaining audience interest and expanding its reach.